Spontaneous resolution of intussusception after COVID-19 infection found at laparoscopy in a 6-year-old - Díaz-Ruiz, Renato (2022)
The incidence of intussusception is 2.5 per 1000 live births, and infants between 4 and 10 months of age represent the highest frequency peak. Cases of intussusception with acute COVID-19 infection have been reported in infants under one year of age and with one death associated with MIS-C. However, we have not found reports of intussusception in schoolchildren. We report the case of a 6-year-old male with two days of illness that began with a sensation of temperature rise, headache, abdominal pain, liquid stools with mucus and no blood, hyporexia, chills, and food vomiting. He presented a negative result for the detection of SARS-CoV-2 antigen, negative SARS-CoV-2 IgM/IgG serology positive (lateral flow immunochromatography test), in addition to total IgM/IgG antibodies in 11.88 COI by means of a test of electrochemiluminescence. An abdominal ultrasound was performed that concluded invagination, for which an exploratory laparoscopy was performed and the patient evolved favorably. 13 cases of intussusception associated with acute COVID-19 infection have been described in this group. However, no reports of intussusception have been described after COVID-19 infection in school age. We recommend ruling out active or past SARS-CoV-2 infection in children with gastrointestinal symptoms and, if it exists, ruling out invagination by means of abdominal ultrasound.